Family functioning and adolescent depression: A moderated mediation model of self-esteem and peer relationships - Huang, Xinquan; Hu, Ningning; Yao, Zhengdong; Peng, Biao (Frontiers in Psychology, 2022)
In consideration of family system theory, the vulnerability model of depression, and the stress buffering model of social support, the current study examined the effect of family functioning on adolescent depression, the mediating effect of self-esteem, and the moderating effect of peer relationships. A sample of Chinese adolescents (n = 562, 47.15% male, 52.85% female, mean age 14.33 years, SD = 1.81 years) completed questionnaires regarding family functioning, depression, self-esteem, and peer relationships. The results showed that: (1) family functioning had a significant negative predictive effect on adolescent depression; (2) self-esteem plays a mediating role between family functioning and adolescent depression; and (3) peer relationships have a moderating effect on the relationship between self-esteem and adolescent depression, supporting the moderated mediation model. These results reveal the influence mechanism of family functioning on adolescent depression and have implications for adolescent depression intervention.